English writing instruction in Iran: Implications for second language writing curriculum and pedagogy - Naghdipour, Bakhtiar (Pergamon-Elsevier Science Ltd, 2016)
This paper reports on English writing instruction and the main factors shaping the dynamics of English writing at different levels of education in Iran. The data gathered from teachers and students using semi-structured interviews and class observations revealed, despite students' need to develop competency in English writing, unsatisfactory writing skills, mainly because of the inadequacy of the English writing curriculum and pedagogy. The findings further indicated that English language education in general and writing skills in particular have fallen prey to the conflict between the post-revolutionary ideological sentiments behind the design and implementation of the English language curriculum and pragmatic forces that allure individuals to subscribe to the new multi-literate and multi-cultural world, which has come to embrace equal educational access and opportunities for its citizens. Exploring the dynamics of English writing in this under-represented context could offer insights for the similar EFL contexts where the role of writing as a means of enriching the personal and future professional life of new generation of students and language learners has yet to be recognized. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: EFL writing; L2 writing instruction; L2 writing curriculum; Iran